New Benzaldehyde and Benzopyran Compounds from the Endophytic Fungus Paraphaeosphaeria sp. F03 and Their Antimicrobial and Cytotoxic Activities * - Amorim, Marcelo R. de [UNESP]; Hilario, Felipe [UNESP]; Santos Junior, Fernando M. dos; Batista Junior, Joaom.; Bauab, Tais M. [UNESP]; Araujo, Angela R. [UNESP]; Carlos, Iracilda Z. [UNESP]; Vilegas, Wagner [UNESP]; Santos, Lourdes C. dos [UNESP] (Georg Thieme Verlag Kg, 2019)
Three new benzaldehyde derivatives, sporulosaldeins A - C ( 1 - 3 ), and 3 new benzopyran derivatives, sporulosaldeins D - F ( 4 - 6 ), were discovered from an endophytic fungus, Paraphaeosphaeria sp. F03, which was isolated from Paepalanthus planifolius leaves. Compounds 1 - 6 were elucidated by 1- and 2-dimensional nuclear magnetic resonance experiments and high-resolution mass spectrometry analysis. The absolute configuration of compound 5 was determined through the comparison of experimental and calculated electronic circular dichroism data. Compounds 1 - 6 were found to exhibit antifungal activity with minimum inhibitory concentration (MIC) values of 7.8 - 250 mu g/mL and racemic mixture of compound 6 exhibited weak cytotoxicity against MCF-7 and LM3 with IC (50) values of 34.4 and 39.2 mu M, respectively.
Keywords: Paraphaeosphaeria sp; F03; benzaldehyde; benzopyran; Paepalanthus planifolius; Eriocaulaceae; endophytic fungus